Exploring motivational orientations of English as foreign language (EFL) learners : a case study in Indonesia - Setiyadi, Ag. Bambang; Wicaksono, B. Anggit; Mahpul, Mahpul (South African journal of education, 2019)
Motivation, which refers to students’ reasons for acting, has been well explored in language learning. However, studies on motivation in language learning in many countries have been predominantly inspired by theories of motivation in learning English developed in western countries. The current study serves to: i) identify the motivational orientations of EFL university students in Indonesia; and ii) to investigate whether the west-inspired theories of motivation are still relevant to the Indonesian EFL students. The subjects of the current study were 886 university students. With alphas .70, .53, and .77 for three motivational orientations, the data were then analysed by running Exploratory Factor Analysis with the varimax rotation. The results showed the existence of three reasonable motivational orientations of the EFL students in Indonesia and they are labelled as extrinsic, international and intrinsic orientation.